Psychotherapy and science - Langs, Robert, 1928-2014 (Perspectives on psychotherapy., 1999)
In this volume, the author argues that theoretical and clinical efforts should be focused on understanding the deep, evolved factors behind human behaviour such as suffering, deception self-limitations and death anxieties.